Investigation of the structure of the set of continuous solutions of systems of nonlinear difference equations with continuous argument - Pelyukh, G. P. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
We study the structure of the set of continuous solutions for one class of systems of nonlinear difference equations with continuous argument in the neighborhoods of equilibrium states.